Morphometrics, body condition, and growth of the ringed seal (Pusa hispida saimensis) in Lake Saimaa: Implications for conservation - Auttila, Miina; Kurkilahti, Mika; Niemi, Marja; Levänen, Riikka; Sipilä, Tero; Isomursu, Marja; Koskela, Jouni; Kunnasranta, Mervi
Morphometrics and growth of the critically endangered Saimaa ringed seal (Pusa hispida saimensis), which inhabits a freshwater lake in Finland were studied using data from 344 carcasses. This study presents the first detailed information on ringed seal pup growth and body condition from birth to the age of one year. Newborn pups were on average 68 cm long and weighed 5 kg. Pups attained the majority of their first year growth during the nursing period. Body condition and growth declined after weaning, but pups recovered from postweaning nutritional deprivation at the age of 8 mo. The seals achieved their maximum body length, girth, and mandible size around the age of 4 yr, and asymptotic body mass two years later. Baculum growth indicated that males reached sexual maturity at age 5-6 yr. The Saimaa ringed seals' asymptotic body length and mass were 132 cm and 59 kg, respectively, which is similar to medium sized marine ringed seals. Saimaa ringed seals' survival to adulthood is extremely low due to high bycatch mortality; furthermore climate change may hamper pup growth and elevate mortality. Therefore we recommend continuation of fishing closures to improve pup survival. 2016